2012
DOI: 10.1021/ja305853d
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Group 14 Element Hydrides in the Activation of C–H Bonds in Cyclic Olefins

Abstract: Formally, triple-bonded dimetallynes ArEEAr [E = Ge (1), Sn (2); Ar = C(6)H(3)-2,6-(C(6)H(3)-2,6-(i)Pr(2))(2)] have been previously shown to activate aliphatic, allylic C-H bonds in cyclic olefins, cyclopentadiene (CpH), cyclopentene (c-C(5)H(8)) and 1,4-cyclohexadiene, with intriguing selectivity. In the case of the five-membered carbocycles, cyclopentadienyl species ArECp [E = Ge (3), Sn (4)] are formed. In this study, we examine the mechanisms for activation of CpH and c-C(5)H(8) using experimental methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 82 publications
1
47
0
Order By: Relevance
“…[7d, 9b] Their critical involvement in the CÀHa ctivation of cyclopentadiene and their reactivity towards C=Cd ouble bonds have been studied by Powera nd co-workers. [12] Recently we becamei nterested in probing the accessibility of low-valent organotin hydride derivatives by selectively removingh ydrogen from tetravalent organotin trihydrides. In this context we werea blet os how that nitrogen bases such as DMAP (4-(N,N-dimethylamino)pyridine) can induce dehydrogenationa nd finally the base adducts of terphenyltin(II) hy-drides were observed.…”
Section: Introductionmentioning
confidence: 99%
“…[7d, 9b] Their critical involvement in the CÀHa ctivation of cyclopentadiene and their reactivity towards C=Cd ouble bonds have been studied by Powera nd co-workers. [12] Recently we becamei nterested in probing the accessibility of low-valent organotin hydride derivatives by selectively removingh ydrogen from tetravalent organotin trihydrides. In this context we werea blet os how that nitrogen bases such as DMAP (4-(N,N-dimethylamino)pyridine) can induce dehydrogenationa nd finally the base adducts of terphenyltin(II) hy-drides were observed.…”
Section: Introductionmentioning
confidence: 99%
“…proceeded without a catalyst . Furthermore, C H activation was also observed by Power et al, who reported an isolation of the {(2,6‐Dipp 2 C 6 H 3 )Ge(η3‐C 5 H 9 )} by the treatment of the digermene {(2,6‐Dipp 2 C 6 H 3 )(H)Ge} 2 with CpH. Jones et al reported on the hydrogermylation reactions of alkenes and alkynes with two‐coordinated germanium(II) hydride {N(Ar)(Si i Pr 3 )}GeH (Figure B) that even reacted reversibly with cycloalkenes .…”
Section: Introductionmentioning
confidence: 74%
“…Instead, the reaction selectively activates the C(sp 3 )À Hb ond in CpH to give 23 [32] or 24 [33] (Scheme 14). The expected Diels-Alder [4+ +2] cycloaddition was not observed.…”
Section: Activation Of Càhb Ondsmentioning
confidence: 99%